Case study of ECOALF: Sustainable Business Model in Fashion Industry - Crnogaj, Katja; Gajšt, Nataša (Študije primerov EPF: Razvoj, trajnost in inovacije v poslovni praksi 2024, 2024)
This case study focuses on sustainable business models and startups by exploring how sustainability can be integrated into the core strategy of a new venture. Sustainable startups, such as ECOALF, are designed to address environmental and social challenges while maintaining profitability. ECOALF, a Spanish fashion brand founded in 2009, exemplifies this approach by transforming waste materials such as plastic bottles, fishing nets and tires into high-quality fashion products. As a B Corp certified company, ECOALF operates within a circular business model, demonstrating that sustainability can be a competitive advantage in the fashion industry. The primary objective of this case study is to analyze ECOALF's sustainable business model and illustrate how the company has successfully balanced environmental and economic goals. By exploring ECOALF's innovative processes, stakeholder partnerships, and strategic initiatives, this case provides insights into how startups can implement sustainable business models to achieve long-term growth and positive environmental impact. It also offers practical lessons for using the Sustainable Business Model Canvas to enhance sustainability in business strategy.